2019
DOI: 10.26599/jnr.2019.9040026
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese medicine-based neurorestorative therapy for Alzheimer’s and Parkinson’s disease

Abstract: The prevalence of multiple neurodegenerative diseases, such as Alzheimer’s disease (AD) and Parkinson’s disease (PD), has been dramatically increasing, particularly in the aging population. However, the currently available therapies merely alleviate the symptoms of these diseases and are unable to retard disease progression significantly. Traditional Chinese medicine (TCM) has been used in clinical practice for thousands of years for ameliorating symptoms or interfering with the pathogenesis of aging- associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…Traditional Chinese medicine (TCM) is considered a huge source of novel drugs and compounds for therapy in neurological diseases [3]. Ginseng (Panax ginseng), a popular herb used in TCM, has been confirmed to play a protective role in cerebral ischemia in vivo [4].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM) is considered a huge source of novel drugs and compounds for therapy in neurological diseases [3]. Ginseng (Panax ginseng), a popular herb used in TCM, has been confirmed to play a protective role in cerebral ischemia in vivo [4].…”
Section: Introductionmentioning
confidence: 99%
“…It may also minimize the side effects of conventional medications. 78,109,140 These benefits may be helpful to lessen suffering and improve the quality of life of animal patients in their aging years. It is hoped that this study will lead to new knowledge and awareness of the potential benefits of TCVM therapy in treating CCD.…”
Section: Discussionmentioning
confidence: 99%
“…Data has showed that the expression of hsa-miR-221-3p, hsa-miR-214-3p, hsa-miR-29c-3p, and miR-124 family is meaningful for the diagnosis of PD [ 7 10 ]. Meanwhile, some scholars believe that miRNA has great potential in treating PD [ 9 14 ]. The abnormal expression of miR-9-5p in neurodegenerative diseases would sabotage its neuroprotective effect [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%